PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN TEKS NARASI MELALUI MODEL SQ3R BERBASIS CULTURALLY RESPONSIVE TEACHING (CRT) PADA SISWA KELAS V SDN 3 BANCARKEMBAR - Azalea Dewi Larassati; Sri Wahjuni Anggara; Subuh Anggoro; Anang Fathoni (LPPM Universitas Bina Bangsa, 2023)
Reading plays a crucial role in acquiring information and knowledge. Through reading, students can gain a better understanding of information or knowledge. Thus, reading comprehension becomes an essential aspect that educators, researchers, and educational observers must pay attention to and implement according to the students' needs. The purpose of this research is to improve students' reading comprehension skills through the SQ3R model based on the Culturally Responsive Teaching (CRT) approach in Indonesian language narrative texts for fifth-grade students at SD N 3 Bancarkembar. This study falls under the category of Classroom Action Research (CAR). The research subjects consisted of 33 fifth-grade students. Data were collected through both tests and non-tests methods and subsequently analyzed using descriptive statistics. The results of the research indicate a significant improvement in reading comprehension skills in each cycle. The achievement rate in the pre-cycle was 32%, then increased to 62% in Cycle I, and further improved to 97% in Cycle II. These findings demonstrate that the use of the SQ3R model based on the Culturally Responsive Teaching (CRT) approach enhances the reading comprehension skills of fifth-grade students at SD N 3 Bancarkembar